5-year remission rate after the discontinuation of adalimumab in patients with rheumatoid arthritis: Long-term follow-up results of the HONOR study. Issue 5 (2nd September 2020) - Yamaguchi, Ayako; Hirata, Shintaro; Kubo, Satoshi; Fukuyo, Shunsuke; Hanami, Kentaro; Nakano, Kazuhisa; Nakayamada, Shingo; Saito, Kazuyoshi; Tanaka, Yoshiya
Abstract: Objectives: To determine the rate and factors associated with remission (disease activity score (DAS) 28-erythrocyte sedimentation rate (ESR) of <2.6) during a 5-year follow-up after the discontinuation of adalimumab (ADA) in patients with rheumatoid arthritis (RA). Methods: 75 patients who had been treated with ADA + methotrexate (MTX) and maintained DAS28-ESR <2.6 for at least 6 months were enrolled. Among them, 52 patients discontinued ADA, and 46 patients completed a 5-year follow-up. Results: During the 5 years, 11 patients had DAS28-ESR <2.6. In 15 patients with DAS28-ESR <3.2, no significant changes were found in the health assessment questionnaire disability index (HAQ-DI) and modified total Sharp score (mTSS). When comparing patients with DAS28-ESR ≤1.61 versus 1.61 <DAS28-ESR <2.6, 50% and 15% of the two groups demonstrated sustained remission, respectively. Remission was more common in patients with shorter disease duration (≤2 years) than those with longer duration (>2 years). Among 31 patients who experienced flare, ADA was restarted in 24 patients, and 17 patients of these achieved DAS28-ESR <3.2 within 1-year. Conclusion: During the 5-year ADA-free period, remission rate was persistent in 21% of the patients. ADA-free remission was possible especially in patients with deeper remission (DAS28-ESR ≤1.61) and shorter disease duration (≤2 years).